The Effect Of Concentration Of Liquid Acid Solution And Length Of Damaging On The Lowering Of Leading Metals (Pb) In Meat Shells ( Anadara granosa) In The Coastal Area Of Makassar City - Alim Syam; Andi Susilawaty; Syarfaini Syarfaini; Munawir Amansyah (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
Shellfish is one of the marine biota that is often consumed by humans. The content of lead heavy metals in Anadara granosa shellfish found in the coastal area of Makassar city is already above the threshold value. Consuming seafood such as shellfish containing heavy metals has a negative effect on humans. One effort that can be done to minimize the content of heavy metals in the body of the shell is by soaking in a solution of lime asama ( Citrus autrantifolia ). Lime acid solution is used because it contains organic compounds that have the ability as chelators (metal binders). The purpose of this study was to see the effect of lime acid solution and soaking time on the reduction of lead levels in the meat of the shellfish. This study uses a Quasi Laboratory Experimental method with a Pre and Post Test with Control Group Design research design . In this study variations in the concentration of lime acid solution used were 50%, 75%, 100% concentration, and 0% concentration as a control. While the variation of soaking time used is 15 minutes, 30 minutes and 60 minutes. The results showed that the treatment dose of 0% of lime acid solution showed a decrease in the levels of lead (Pb) the lowest, namely at the time of treatment for soaking for 60 minutes as much as 0.0467 mg / kg . Whereas the treatment dose of 100 % and soaking time for 60 minutes showed the most effective treatment in reducing lead levels in shellfish meat, which was 1,1600 mg / kg. Keywords: Anadara granosa , Pb  , Citrus autrantifolia